Dynamics of the Earth's Radiation Belts and Inner Magnetosphere. - Summers, Danny (Wiley, 2013)
Published by the American Geophysical Union as part of the Geophysical Monograph Series. Dynamics of the Earth's Radiation Belts and Inner Magnetosphere draws together current knowledge of the radiation belts prior to the launch of Radiation Belt Storm Probes (RPSP) and other imminent space missions, making this volume timely and unique. The volume will serve as a useful benchmark at this exciting and pivotal period in radiation belt research in advance of the new discoveries that the RPSP mission will surely bring. Highlights include the following: a review of the curre.